Explorando el potencial del litio peruano: retos y oportunidades - Rivera Daza, Pamela (2023)
The article explores the potential of lithium in Peru, addressing the challenges and opportunities to achieve sustainable development and generate economic and social impact. Peru has significant lithium reserves, but the lack of clear and effective regulation has limited foreign investment. The importance of addressing social and environmental issues is highlighted. In addition, the relevance of lithium in the manufacture of rechargeable batteries for electric vehicles and renewable energy storage systems is discussed. Finally, the article concludes that the potential of lithium to contribute to the transition towards a low carbon economy is considerable but requires a coherent and transparent strategy to guarantee its sustainable exploitation.